Tillage Intensity in a Long-Term Wheat- Sorghum-Fallow Rotation - A. Schlegel (Kansas Agricultural Experiment Station Research Reports, 2016)
Grain yields of wheat and grain sorghum increased with decreased tillage intensity in a wheat-sorghum-fallow (WSF) rotation. In 2015, available soil water at wheat planting was greater for no-till (NT) and reduced till (RT) than for conventional till (CT). Similarly, for grain sorghum in 2015, available soil water at planting was increased with NT or RT and least with CT. Averaged across the 15-yr study, available soil water at wheat and sorghum planting was similar for RT and NT and about 1 inch greater than CT. Averaged across the past 15 years, NT wheat yields were 5 bu/a greater than RT and 7 bu/a greater than CT. Grain sorghum yields in 2015 were 42 bu/a greater with long-term NT than short-term NT. Averaged across the past 15 years, sorghum yields with long-term NT have been nearly twice as great as short-term NT (64 vs. 35 bu/a).
Keywords: tillage intensity; wheat-sorghum-fallow rotation; reduced till; conventional till; no till